Prevention of quality loss and melanosis of white leg shrimp by Sargassum horneri extracts. Issue 7 (24th February 2021) - Fang, Hua; Zhang, Jianyu; Hong, Zhuan; Chen, Weizhu; Zhang, Yiping; Fang, Meijuan
Abstract : Purpose: Being interested in developing a natural preservative for the prolongation of shrimp shelf life, this study aims to evaluate the Sargassum horneri extracts for their antioxidant effect, copper reducing power, copper chelating activity and polyphenol oxidase (PPO) inhibitory activity, as well as explored their potential preservative activity in white leg shrimp. Design/methodology/approach: The antioxidant properties of Sargassum horneri 75% ethanol aqueous extracts were measured by 2, 2-diphenyl-1-picryl hydrazyl (DPPH), 2, 2-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP) and PPO inhibitory activity. Sample III displayed the highest antioxidant activity, PPO inhibitory activity, copper reducing power and copper chelating activity, so it was selected for further studying its impact on shrimp's quality changes such as pH value, total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), melanosis and sensory score during storage at 4°C. Findings: Among all three samples, sample III containing 49.88% total phenolic contents was selected for the further study on the prevention of quality loss and melanosis of shrimp, because it yielded the highest antioxidant activity, PPO inhibitory activity, copper reducing power and copper chelating activity than the other two samples (samples II and IV). It was found that shrimp treated with 0.2% sample III had the lowest melanosis scores throughout the storage ( p  < 0.05). During ten days of storage at 4°C, shrimp treated with 0.2% sample III had a higher score in sensory properties (color, segments, texture and odor), compared with the control, 0.1% kojic acid and 0.1% sample III treated shrimp ( p  < 0.05). The results indicated that the treatment of shrimp with 0.2% sample III could extend the shelf life to eight days at 4°C. Social implications: The extracts of Sargassum horneri displayed potent PPO inhibition, antimicrobial and antioxidant properties. Importantly, the 75% extracts of Sargassum horneri could extend the shelf life. Considering these results, the extracts of Sargassum horneri may be used as natural preservatives in the food industry after further evaluation of their other properties such as toxicity, as well as provide a choice target to source natural products intended for cosmetics. Originality/value: The originality of this paper lies in the development and application of the extracts of edible algae. To extend the shelf life of seafood, the polyphenolic-rich extract of Sargassum horneri provided another possible selection.